Peloidtherapy in older adults with knee osteoarthritis. Yaguaramas, 2021 - Maydelin Pérez Reina; Isidro Matos Lamote; Mailyn Montero Morales; Jorge Enrique Rodríguez León; Julián Sobral Rey; Esther Yarinely Hernández Diéguez (Medisur)
Background: the increase in life expectancy is coupled with the elderly’s need to function in its media and guarantee full longevity. Objective: to determine the effectiveness of peloidtherapy in older adults with osteoarthritis of the knee. Method: a quasi-experimental intervention study was carried out in 30 patients with osteoarthritis of the knee, selected by simple randomization, who were treated in the health area of Yaguaramas (Abreus, Cienfuegos), between March and June of 2021. A general survey was carried out. The evolution of pain was determined using the Likert scale, and joint limitation was analyzed by measuring the knee joint arc with the goniometer. Results: there was a predominance of patients in the age group of 66-70 years old and of the female sex; with evolution time between 5-10 years (60%); and with both knees affected (56.7%). The main signs and symptoms were pain (100%) and limitation of joint movement (93.3%), which decreased after treatment. 53.3% reported light pain before treatment; after treatment, 83.3% described absence of pain. 76.7% of the patients manifested limitation in knee flexion, which after treatment decreased to 13.3%. Conclusions: peloidtherapy has a positive influence on older adults with osteoarthritis of the knee, by improving their functional status and personal independence, as well as reducing the demands for medical services.